ANALISIS PENGARUH DANA ALOKASI UMUM (DAU) DAN PENDAPATAN ASLI DAERAH (PAD), TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN DELI SERDANG DENGAN BELANJA DAERAH SEBAGAI VARIABEL INTERVENING - Harahap, Rahmat Daim; Harahap, Muhammad Ikhsan; Syari, Meilya Evita (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2019)
The government hold significant role in the implementation of fiscal economy policy to achieve the main goal of development: high economic growth, decrease of unemployment, and control of inflation, income and expenditure that can be used in increasing economic growth. Regional incomes are locally-generated revenue, General Allocation Fund. Meanwhile, cost is regional expenditures. Thus, this study is aimed to determine the influence of the General Allocation Fund and Regional income on economic growth with the role of Regional Expenditure as an intervening variable. The study was located on Deli Serdang Regency. This is a quantitative research with multiple linear regression analysis by using SPSS. The result shows that General Allocation Fund and Regional income influence the economic growth, meanwhile regional expenditures mediates between General Allocation Fund and Regional income on economic growth.